Experimental study on axial compressive behavior of concrete-filled corrugated steel tubular columns - Tong, Jing-Zhong; Zhang, Jia-Ming; Yu, Chao-Qun; Wu, Ruo-Min; Tong, Gen-Shu; Chen, Ming; Gao, Wei (Engineering structures, 2024)
Concrete-filled corrugated steel tubular (CFCST) column is a novel type of steel-concrete composite column, comprising four corrugated steel plates, four square-section steel bars at the corners, and infilled concrete. The transversely placed corrugated steel plates can effectively prevent their premature local buckling, release the axial load, and provide lateral confinement effects on the infilled concrete. This paper investigated the axial compressive behavior of CFCST columns through experimental, numerical, and theoretical approaches. Experiments were conducted on 20 specimens, focusing on their axial load-resistant behavior. The specimens demonstrated excellent axial bearing capacity, ductility, and residual bearing capacity. Besides, the mechanical behavior of corrugated steel plates throughout the loading process was analyzed through the development of the horizontal and vertical strains. Furthermore, a finite element (FE) model was developed to simulate the axial compressive behavior of CFCST columns, which was validated against the experimental data. The FE model was used to analyze the compressive behavior of each part in CFCST columns, revealing that the infilled concrete and steel bars primarily bear the axial load, while the corrugated steel plates mainly provide lateral supports to the infilled concrete. Finally, a simplified method for calculating the critical width of corrugated steel plates and a formula for the axial bearing capacity of CFCST columns were proposed. It was indicated that the limiting width-to-thickness ratio of the corrugated steel plates was larger than that of the steel elements in conventional CFST columns. These formulas were demonstrated to be accurate enough and suitable for the engineering designs. •Axial compression tests involving 20 CFCST columns were performed.•Finite element models were developed and validated against test results.•The mechanical behavior of each part of the CFCST column was analyzed in detail.•A theoretical analysis was conducted to determine the critical width of the corrugated steel plate.•Theoretical formula of the axial bearing capacity of the CFCST columns was proposed.